Pendekatan Terapi Hyperbaric Oxygen Therapy pada Pasien dengan Polycystic Ovary Syndrome - Nurdianto, Arif Rahman; Harnanik, Titut; Setiawan, Fery (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2024)
Background: Polycystic Ovary Syndrome (PCOS) is an endocrine disorder affecting around 5-10% of women of reproductive age. Symptoms of PCOS include menstrual irregularities, infertility, and elevated androgen levels. Various therapies have been explored to address these issues, one of which is Hyperbaric Oxygen Therapy (HBOT), known for its ability to enhance tissue healing, reduce inflammation, and improve hormonal balance. However, the effects of HBOT on PCOS patients require further investigation. Objective: This study aims to explore the effectiveness of Hyperbaric Oxygen Therapy in reducing PCOS symptoms and improving patients' quality of life. Method: This research employs a literature review methodology, collecting data from various relevant articles and journals on Hyperbaric Oxygen Therapy in PCOS patients. The sources were selected based on strict inclusion criteria, focusing on studies that examine the physiological and hormonal effects of HBOT on PCOS patients. Results: The reviewed studies suggest that HBOT shows potential in reducing PCOS symptoms, particularly in regulating menstrual cycles and lowering androgen levels. Other positive effects include improved insulin sensitivity and ovarian health. However, further research with larger sample sizes and long-term follow-ups is necessary to provide more consistent results. Conclusion: Hyperbaric Oxygen Therapy could be a potential adjunctive treatment for PCOS patients, though more research is needed to confirm its long-term benefits and underlying mechanisms